REPRESENTASI KESEDIHAN DALAM LIRIK LAGU KARYA N-BUNA: KAJIAN DIKSI DAN GAYA BAHASA - Rai Putri Kartika Sari; Ketut Yarsama (Stilistika : Jurnal Pendidikan Bahasa dan Seni, 2023)
This research is entitled "Representation of Sadness in the Lyrics of Songs By N-Buna". The purpose of this research is to examine the form of diction and language style in the lyrics of the song Ai Nijou, Dakara Boku wa Ongaku o Yameta, and Kokoro ni Ana ga Aita. The methods used in this research were the literature study method and the informal method. This research used the theory of stylistic proposed by Sudjiman, theory of diction and theory of language style proposed by Keraf. The results of this research indicates there were form of diction represent of sadness, namely denotative diction and connotative diction. Aside from that, there were language style, namely simile, methaphor, allegory and personification language styles. The dominant diction used to represent of sadness is connotative diction. Therefore, the dominant language style used to represent of sadness is metaphor and personification language styles.